2006
DOI: 10.1097/01.mpg.0000189353.40419.31
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Comparing Oral Sodium Phosphate Solution to a Bowel Cleansing Preparation with Nutrition Food Package in Children

Abstract: Although both regimens were comparable in adequacy of colon visualization, preparation tolerance, side effects and compliance profile in this pilot study, the prepackaged diet kit with magnesium citrate/bisacodyl laxative resulted in superior colon cleansing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…Th e bowel cleansing eff ectiveness of NaP was superior to PEG in 1 study ( 207 ) and similar in another study ( 208 ). In a randomized study comparing a prepackaged diet kit including magnesium citrate and bisacodyl laxatives with NaP, the 2 regimens had comparable tolerability, although the quality of cleansing was superior with the magnesium citrate regimen ( 210 ). Th e Israeli Society of Pediatric Gastroenterology and Nutrition reviewed the evidence of adverse events with oral NaP and recommended that NaP should not be used in children younger than 12 years of age, children with any type of kidney disease, children treated with medications that aff ect renal function, children with signifi cant comorbidities (eg, liver disease, hypertension, hypoparathyroidism, diabetes, and heart disease), children at high risk for dehydration or electrolyte imbalance, and children with ileus or suspected severe colitis ( 211 ).…”
Section: Pediatricsmentioning
confidence: 76%
“…Th e bowel cleansing eff ectiveness of NaP was superior to PEG in 1 study ( 207 ) and similar in another study ( 208 ). In a randomized study comparing a prepackaged diet kit including magnesium citrate and bisacodyl laxatives with NaP, the 2 regimens had comparable tolerability, although the quality of cleansing was superior with the magnesium citrate regimen ( 210 ). Th e Israeli Society of Pediatric Gastroenterology and Nutrition reviewed the evidence of adverse events with oral NaP and recommended that NaP should not be used in children younger than 12 years of age, children with any type of kidney disease, children treated with medications that aff ect renal function, children with signifi cant comorbidities (eg, liver disease, hypertension, hypoparathyroidism, diabetes, and heart disease), children at high risk for dehydration or electrolyte imbalance, and children with ileus or suspected severe colitis ( 211 ).…”
Section: Pediatricsmentioning
confidence: 76%
“…69 PEG-3350 without electrolytes was shown to be efficacious in more than 90% of pediatric patients when used over a 4-day period. 20 An NaP solution was found to be less effective when compared with magnesium citrate used with a low-residue diet in one study, 70 although equally effective and more acceptable when compared with the same medication in addition to an enema. 71 Various other regimens, including senna or magnesium citrate with enema 27 and bisacodyl with enema, 72,73 were found to be efficacious in open-label prospective trials.…”
Section: Outcomes Data and Comparative Studiesmentioning
confidence: 97%
“…Indeed, nearly all of the reported adverse outcomes with Fleet products in children occurred following enema administration [8,9] and not because of orally administered NaP. In addition, several prospective trials in pediatric patients [5,10,11] have found that oral NaP is a safe preparation for colonoscopy in children. These studies included children as young as three years of age; however, the degree of hyperphosphatemia observed in children was greater than that reported in adults [5].…”
mentioning
confidence: 96%